Use of health services following self-harm in urban versus suburban and rural areas: a national cross-sectional study. Issue 7 (26th July 2013) - Fadum, Elin Anita; Stanley, Barbara; Rossow, Ingeborg; Mork, Erlend; Törmoen, Anita J; Mehlum, Lars
Abstract : Objectives: This study examines whether there is a difference between urban versus suburban and rural adolescents in their use of health services following two types of self-harm distinguished as self-harm with or without suicide intent. Setting: A nationwide cross-sectional school survey of 11 406 Norwegian adolescents aged 13–19 years in 73 Norwegian junior and senior high schools. Participants: Adolescents who reported self-harm and provided valid responses to a follow-up question about having received subsequent help or treatment (n=959) were included in the study. Adolescents were divided into urban versus suburban and rural depending on: (1) the location of municipalities where they attended school and (2) the place of residence. Associations between urban versus suburban and rural areas and the use of health services following self-harm were assessed in those who self-harmed with and without suicide intent. Primary outcome measure: Use of health services following self-harm. Results: 1 in 4 adolescents reported using health services following self-harm. Adolescents reporting self-harm with suicide intent were more likely to use health services than those who self-harmed without suicide intent. Following self-harm without suicide intent, adolescents in urban areas were four times more likely to use health services than adolescents in suburban and rural areas. There was no statistically significant area difference in the use of health services following self-harm with suicide intent. Conclusions: This study found a geographical variation in the use of health services following self-harm without suicide intent, but not following self-harm with suicide intent. Differences in perception of self-harm and help-seeking behaviour between areas and different accessibility to services are suggested as possible explanations. There is a need to better understand how the interplay between individual characteristics and accessibility to services influences adolescents' use of health services following self-harm. We suggest that multilevel models are a valuable approach to achieve this goal.